Reading strategies for college English language learners - Cruz-Zambrano, Mónica Cecilia; Delgado-Morán, Rocío Carolina; Quiroz-Cevallos, Jenny Elizabeth; Rincón-Zambrano, Rodrigo Alexander (Revista Arbitrada Interdisciplinaria Koinonía, 2023)
This research focused on determining the effectiveness of reading strategies for English university students, such as previewing, scanning, skimming, prediction and inference, with the purpose of perceiving the changes in their reading comprehension and other skills after the application of these strategies. As methodology, a quantitative approach based on a quasi-experimental design was used. For this purpose, a sample of 60 students from the Metropolitan University of Quito, Ecuador, were subdivided into 30 for the control group and 30 for the experimental group, to whom pretest and posttest were applied. The results revealed that the students in the control group did not achieve considerable improvements but those in the experimental group did. The skills developed were: vocabulary, interpretation, comprehension, identification of main and secondary ideas, fluency and summarizing.